CCSK Cert Prep: 1 Cloud Architecture. - Lachance, Daniel (linkedin.com, 2021)
This course helps you prepare for the Certificate of Cloud Security Knowledge (CCSK) exam and is also useful to IT technicians who plan the use of cloud computing services.